The complexity of speaking anxiety among students in an international university in Thailand - Jebamani Anthoney; Jeffrey Wilang (English Language Teaching Educational Journal, 2023)
Prior research has shown that English as a Foreign Language (EFL) students often experience speaking anxiety and its detrimental effects. However, there is limited knowledge about the speaking anxiety experienced by international students at a Thai university where English serves as both the medium of instruction and the primary language of communication outside the classroom. This study employed a three-pronged approach: a survey questionnaire to gauge speaking anxiety levels and identify differences based on nationality and geographical location; sorting activities to observe changes in speaking anxiety levels; and individual interviews to gain a deeper understanding of students' speaking anxiety. The descriptive analysis showed that students experienced varying degrees of anxiety. Among the 13 nationalities surveyed, Vietnamese, Cambodian, Thai, and Burmese students displayed higher levels of speaking anxiety. Moreover, students from rural backgrounds were more anxious than those from urban areas. Interviews conducted after the sorting activities revealed that factors such as familiarity, predictability, competence, and social support influenced students' anxiety levels. Pedagogical recommendations include the importance of repetition and practice, scaffolding, familiarity with an activity, building positive relationships, incremental exposure to language activities, regulating emotions and encouraging reflective practices.